2012
DOI: 10.1074/jbc.c112.353946
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated Isocitrate Dehydrogenase Mutations Inactivate NADPH-dependent Reductive Carboxylation

Abstract: Background:Reductive carboxylation by isocitrate dehydrogenase (IDH) is required for hypoxic growth, and IDH mutations are associated with cancer. Results: Reductive carboxylation by IDH is inhibited by NADP ϩ and isocitrate and inactivated by cancer-associated mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
137
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(146 citation statements)
references
References 30 publications
6
137
0
1
Order By: Relevance
“…3a). Employing previously reported reaction conditions with Tris-based buffers 31 , we detected substantial non-enzymatic production of 2HG that was equally distributed as D- and L- enantiomers (Supplementary Fig. 6).…”
Section: Resultsmentioning
confidence: 64%
“…3a). Employing previously reported reaction conditions with Tris-based buffers 31 , we detected substantial non-enzymatic production of 2HG that was equally distributed as D- and L- enantiomers (Supplementary Fig. 6).…”
Section: Resultsmentioning
confidence: 64%
“…Previous studies have demonstrated that IDH1 R132H human gliomas maintain normal concentrations of α-KG but have not identified a mechanism that compensates for diverted flux of α-KG into 2-HG (8,9,18,19). In human tumors, mutations in IDH1 and IDH2 are mutually exclusive and invariably heterozygous (7).…”
Section: Idh1mentioning
confidence: 99%
“…Mutant mice overexpressing IDH1 in liver and adipose tissue are obese, have fatty livers, and show elevated plasma triglycerides (TG) and cholesterol (7). In tumor cells, IDH1 contributes to de novo lipogenesis by generating acetyl-CoA building blocks via the NADPH-dependent reductive carboxylation of α-KG to isocitrate (8)(9)(10)(11). However, IDH1-null mice at steady-state are healthy and fertile, maintain normal body weight, and show no inflammatory symptoms (12).…”
mentioning
confidence: 99%